Formulation and evaluation of lecithin organogel for treatment of arthritis - Jatav, Mahendra Prasad; Ramteke, Suman (International Journal of Scientific World, 2015)
Background: Arthritis is a disease of the joint that involves inflammation of one or more joints. Topical administration of NSAIDs could deliver lornoxicam to the site of action in rheumatic diseases, which would reduce the gastrointestinal complications and side effects of the drug.Methods: In this method, the oily phase was prepared by dispersing the specific amount (ratio; 40:60) of purified lecithin at room temperature in isopropyl myristate as dispersing and emulsifying agent. The aqueous phase of polypropylene was prepared by dispersing a weighed amount of polypropylene and glycerol in water. It was stored at 2-4 oC overnight for the effective dissolution. The aqueous phase was slowly added in oily phase with stirring at 400 rpm using a mechanical stirrer. The prepared organogel of lornoxicam were evaluated for its appearance, organoleptic characteristic, viscosity, gelation temperature, drug content and in vitro release study. In vivo evaluation for analgesic activity of formulation was carried out in terms of skin irritation study, hot plate method; writhing test and edema paw induce method.Results: The drug content of organogel formulations was found in the range of 92.43±2.10-97.93±0.31% indicating uniform distribution of drug through the base and no interaction of drug with component of base. Posthoc Dunnet’s t-test by employing statistical software, GraphPad InStat 3. It’s shown differences between groups were considered significant at P < 0.05.Conclusion: The transdermal organogel formulation of lornoxicam could provide significant anti-inflammatory and antirheumatic activity when applied topically and was observed to be functional for topical delivery of lornoxicam.